Typhoid fever in nineteenth-century Colombia: Between medical geography and bacteriology (2014)
This paper analyses how the Colombian medical elites made sense of typhoid fever before and during the inception of bacteriological ideas and practices in the second half of the nineteenth century. Assuming that the identity of typhoid fever has to be understood within the broader concerns of the medical community in question, I show how doctors first identified Bogotá's epidemics as typhoid fever during the 1850s, and how they also attached specificity to the fever amongst other continuous fevers, such as its European and North American counterparts. I also found that, in contrast with the discussions amongst their colleagues from other countries, debates about typhoid fever in 1860-70 among doctors in Colombia were framed within the medico-geographical scheme and strongly shaped by the fear of typhoid fever appearing alongside 'paludic' fevers in the highlands. By arguing in medico-geographical and clinical terms that typhoid fever had specificity in Colombia, and by denying the medico-geographical law of antagonism between typhoid and paludic fevers proposed by the Frenchman Charles Boudin, Colombian doctors managed to question European knowledge and claimed that typhoid fever had distinct features in Colombia. The focus on paludic and typhoid fevers in the highlands might explain why the bacteriological aetiology of typhoid fever was ignored and even contested during the 1880s. Anti-Pasteurian arguments were raised against its germ identity and some physicians even supported the idea of spontaneous origin of the disease. By the 1890s, Pasteurian knowledge had come to shape clinical and hygienic practices. © 2014 the Author(s).